Partial Replacement of Cement with Glass Bottle Waste Powder in Concrete for Sustainable Waste Management: A Case Study of Kumasi Metropolitan Assembly, Ashanti Region, Ghana - Nyantakyi, Emmanuel Kwesi; Obiri-Yeboah, Abena; Mohammed, Ghadafi Abdullai (Journal of Civil Engineering Research, 2020)
The objective was to investigate partial replacement of single and mixed coloured waste glass bottle powder for cement in concrete technology. Ordinary Portland cement in concrete mix was replaced with bottle glass waste powder of 30%, 50% and 70% respectively during mixing. A mix design ratio of 1:2:4 with water-to-cement ratio of 0.6 and design strength of 20MPa was used. Concrete cubes of sizes 150mmx150mmx150mm were cast and slump tested. Compressive strength density and percentage of water absorption test for concrete curing ages at 7- and 28-days were determined respectively. The slump test results showed decreasing slump values with increasing proportions of glass bottle waste powder. Further tests on the concrete specimen showed decreased compressive strength, density and percentage of water absorption values as glass bottle waste powder in concrete increased as compared to the control concrete mix. Replacement of glass bottle powder of 30% for cement in the concrete showed an enhanced performance when compared with the other percentage ratios used as well as the control mix. The study therefore recommends a 30% glass bottle waste powder to replace cement. The study recommends a study of the replacement over a longer period to verify the properties obtained.
Keywords: Replacement; Glass Bottle Waste Powder; Concrete Technology; Sustainable Waste; po; Ghana; University of Energy & Natural Resources; ACE: Energy and Environmental Sustainability